Manipulating Active Structure and Function of Cationic Antimicrobial Peptide CM15 with the Polysulfonated Drug Suramin: A Step Closer to in Vivo Complexity. (20th May 2019) - Quemé‐Peña, Mayra; Juhász, Tünde; Mihály, Judith; Cs. Szigyártó, Imola; Horváti, Kata; Bősze, Szilvia; Henczkó, Judit; Pályi, Bernadett; Németh, Csaba; Varga, Zoltán; Zsila, Ferenc; Beke‐Somfai, Tamás
Abstract: Antimicrobial peptides (AMPs) kill bacteria by targeting their membranes through various mechanisms involving peptide assembly, often coupled with disorder‐to‐order structural transition. However, for several AMPs, similar conformational changes in cases in which small organic compounds of both endogenous and exogenous origin have induced folded peptide conformations have recently been reported. Thus, the function of AMPs and of natural host defence peptides can be significantly affected by the local complex molecular environment in vivo; nonetheless, this area is hardly explored. To address the relevance of such interactions with regard to structure and function, we have tested the effects of the therapeutic drug suramin on the membrane activity and antibacterial efficiency of CM15, a potent hybrid AMP. The results provided insight into a dynamic system in which peptide interaction with lipid bilayers is interfered with by the competitive binding of CM15 to suramin, resulting in an equilibrium dependent on peptide‐to‐drug ratio and vesicle surface charge. In vitro bacterial tests showed that when CM15⋅ suramin complex formation dominates over membrane binding, antimicrobial activity is abolished. On the basis of this case study, it is proposed that small‐molecule secondary structure regulators can modify AMP function and that this should be considered and could potentially be exploited in future development of AMP‐based antimicrobial agents. Abstract : Disorder to order : Antimicrobial peptides (AMPs) experience complex environments in their hosts, and this can significantly affect their function. The cationic AMP CM15 forms a tight complex with the polyanionic drug suramin, affecting its structure upon membrane binding. This case study demonstrates with three‐component systems that modulation of the AMP's structure also changes its antibacterial activity.